CYBER SECURITY INVESTMENT - Dujam Kovač (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
Accelerated development of technologies and their more frequent application within business organizations create numerous advantages in terms of speed of execution and automation of business processes, easier access and exchange of information, performing business activities remotely, easier access to markets, reducing business costs, etc. At the same time, business organizations are exposed to cyber risks and threats that are becoming more diverse, more complex and are growing steadily. Various forms of cyber risks are manifested through the compromise of information systems of business organizations, which can cause significant direct and indirect financial losses. Although there are growing vulnerabilities to cyber risks, especially in terms of their intensity of impact on the operations of organizations, there is still a lack of cyber security management activities. Many business organizations ignore or underestimate cyber risks or rely on generic security products. Despite the fact that cyber risks are becoming an increasingly important factor infl uencing the operations of organizations and their performance, research in the economic literature and in its narrower field of risk management is not adequately represented. The aim of this paper is to provide an overview of research in the field of investing in cyber security as a loss control, which is an indispensable prerequisite for confidentiality, availability and integrity of information and information systems. Furthermore, the aim of this paper is to compare investment in cyber security with the method of financial control and emphasize the importance of combining these two methods in achieving cyber security.